2013
DOI: 10.1111/ped.12028
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of irritable bowel syndrome

Abstract: Background: Chronic diarrhea and functional abdominal pain (FAP) in childhood could be an early manifestation of adult irritable bowel syndrome (IBS). The aim of this study was to investigate the presence of chronic functional digestive symptoms in childhood, interviewing adult patients diagnosed with IBS, in an attempt to establish a relationship between them. Methods: By means of a questionnaire, the history of colic, chronic diarrhea, functional abdominal pain, constipation and migraine in childhood, was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…All of them were published in English language. Two studies included adult patients [21, 22], and 5 trials enrolled pediatric population [1012, 20, 23]. Only one study did not indicate age of the included studies [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them were published in English language. Two studies included adult patients [21, 22], and 5 trials enrolled pediatric population [1012, 20, 23]. Only one study did not indicate age of the included studies [11].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study did not indicate age of the included studies [11]. The diagnosis of infant colic was made based on medical history provided by parents in 4 trials [10, 11, 20, 23], two studies confirmed infant colic through follow-up visiting and diagnosis by physicians [22, 24], and one study got the record from examinee questionnaire [21]. All the studies compared the occurrence of colic in migraine and control groups, and 2 trials of them also recorded that in TTH patients [10, 11].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six articles were identified in the PubMed searches. Three studies met inclusion criteria for the primary analysis (11,18,19) and an additional two met inclusion criteria for the secondary analysis (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts at prevention of IBS is a challenge and a future opportunity to reduce the disease burden and minimize the wastage of large sums of public funds. It has been shown that a significant proportion of adults with IBS had childhood chronic abdominal pain and possibly IBS[ 251 ]. Therefore, the attempt to prevent FAPDs including IBS in childhood possibly have a compound effect to minimize economic burden of adults with IBS as well.…”
Section: Preventionmentioning
confidence: 99%